UNFULFILLED SEXUAL DESIRE BHATARA GURU KEPADA DEWI UMA SEBAGAI REPRESENTASI PENYEBAB FENOMENA PERSELINGKUHAN MASA KINI - Mohamad Juniawan Sapputra; Adhimas Hayyun Pradhipa (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Unfulfilled sexual desire can trigger infidelity in marital relationships, influenced by psychological, social, and cultural factors. This study aims to analyze the causes and impacts of infidelity through the relationship of Bathara Guru and Dewi Uma in Serat Paramayoga as a representation of contemporary phenomena. The study uses a qualitative approach with a philological method, supported by interviews with three married female informants. The findings show that unfulfilled sexual desire, dominance of instinctual drives (id), lack of communication, and external temptations are the main factors leading to infidelity. The impacts include marital conflict, domestic violence, and changes in relationship dynamics. This study emphasizes the importance of communication, self-control, and balanced fulfillment of emotional and sexual needs to maintain harmony in marital relationships.